Early Root Transcriptomic Changes in Wheat Seedlings Colonized by Trichoderma harzianum Under Different Inorganic Nitrogen Supplies - Rubio, M. Belén; Martínez de Alba, A. Emilio; Nicolás, Carlos; Monte, Enrique; Hermosa, Rosa (Frontiers in Microbiology, 2019)
Wheat is one of the most important crops worldwide. The use of plant growth promoting microorganisms such as those of the genus Trichoderma constitutes an alternative to chemical fertilizers, since they are cheaper and not detrimental to the environment. However, the interaction between Trichoderma and wheat plants has been scarcely studied, at least at a molecular level. In the present work, a microarray approach was used to study the early transcriptomic changes induced in wheat roots by Trichoderma harzianum applied alone or in combination with different concentrations of calcium nitrate [Ca(NO3)2], this last used as nitrogen (N) source. Our results show that T. harzianum causes larger transcriptomic changes than Ca(NO3)2 in wheat roots, and such changes are different when plants are challenged with Trichoderma alone or are treated with a combination of T. harzianum and Ca(NO3)2. Overall, T. harzianum activates the expression of defense-related genes at early stages of the interaction with the roots, while this fungus reduces the expression of genes related to plant growth and development. Moreover, the current study in wheat roots subjected to the different T. harzianum and Ca(NO3)2 combinations reveals that the number of transcriptomic changes was higher when compared against those caused by the different Ca(NO3)2 concentrations than when it was compared against those caused by T. harzianum. N metabolism gene expression changes were in agreement with the levels of nitrate reductase activity measured in plants from Trichoderma plus Ca(NO3)2 conditions. Results were also concordant with plant phenotypes, which showed reduced growth at early interaction stages when inoculated with T. harzianum or with its combination with Ca(NO3)2 at the lowest dosage. These results being in a good agreement with the recognized role of Trichoderma as inducer of plant defense.